Mengokohkan Kemandirian Desa: Pelatihan Peningkatan Kapasitas Aparatur Pemerintahan Desa - Olis Olis (LPPM - STT Kadesi Bogor, 2024)
Village governance plays a central role in managing local affairs at the rural level, encompassing administration, infrastructure development, basic services, and community empowerment. This research focuses on capacity-building training for the officials of Sukajadi Village government to strengthen their administrative functions. Through a Pancasila-based approach, this training aims to enhance the understanding and skills of officials in carrying out administrative tasks effectively. The training methodology involves program development, training sessions using presentation methods and interactive discussions, and evaluations to improve the quality of activities. It is hoped that this training will assist the officials of Sukajadi Village government in providing better services to the community and strengthening village administration management, in line with the vision of inclusive and sustainable development